Gender and Educational Philanthropy
XVI, 261 p.
Keywords: This book explores the complex questions facing funding agencies and foundations as they grapple to understand and define gender equity in education. It covers different approaches funders use to define gender equity, target limited resources, and create collaborative relationships that will ultimately make schools equitable and engaging for all.